Setting Strategic Priorities for Ethnic Community-Based Tourism Using Integrated Rural Accessibility Planning - Taufik Raharjo; Roby Syaiful Ubed; Mulyadi Mulyadi; Hakim Arif Rahman; Muhammad Setiawan Kusmulyono (International Research Journal of Business Studies, 2026)
This study identifies the development priorities of Kepuhsari, an ethnic community-based tourism (ECBT) village in Indonesia, by assessing infrastructure accessibility and examining the role of Village-Owned Enterprises (BUMDesa). This study uses a quantitative descriptive approach based on the Integrated Rural Accessibility Planning (IRAP) method, complemented by qualitative methods, including FGDs, interviews, observation, and secondary data, to generate weighted accessibility indicators. The findings indicate that transportation infrastructure and public information media are the most critical priorities in both upper and lower village regions. However, BUMDesa Sido Mukti remains inactive in tourism development due to managerial constraints and misalignment with ECBT objectives. This study uniquely applies IRAP, traditionally used for rural infrastructure, to ethnic tourism development. Practically, this study recommends enhancing transportation and information infrastructure, alongside restructuring the strategic direction of BUMDesa. Methodological limitations include context-specific findings that cannot be statistically generalized without reapplying the full IRAP process in other settings.